By-product identification and phytotoxicity of biodegraded Direct Yellow 4 dye. (February 2017) - Nouren, Shazia; Bhatti, Haq Nawaz; Iqbal, Munawar; Bibi, Ismat; Kamal, Shagufta; Sadaf, Sana; Sultan, Misbah; Kausar, Abida; Safa, Yusra
Abstract: Citrus limon peroxidase mediated decolourization of Direct Yellow 4 (DY4) was investigated. The process variables (pH, temperature, incubation time, enzyme dose, H2 O2 amount, dye concentration, co-metal ions and surfactants) were optimized for maximum degradation of dye. Maximum dye decolourization of 89.47% was achieved at pH 5.0, temperature 50 °C, enzyme dose 24 U/mL, H2 O2 concentration 0.25 mM and DY4 concentration 18.75 mg/L and incubation time 10 min. The co-metal ions and surfactants did not affect the dye decolourization significantly. Response surface analysis revealed that predicted values were in agreement with experimentally determined responses. The degradation products were identified by UPLC/MS analysis and degradation pathway was proposed. Besides, phytotoxicity assay revealed a considerable detoxification in response of biodegradation of DY4 dye. C . limon showed promising efficiency for DY4 degradation and could possibly be used for the remediation of textile effluents. Graphical abstract: Highlights: Direct Yellow 4 was undergone to biodegradation using C . limon peel peroxidase. Statistical tools was used for optimization of degradation conditions. Metabolites were identified and a degradation mechanism was proposed. At optimum conditions, up to 89% degradation of DY4 was achieved. Metabolites were found less toxic than the original dye.